Systematic Literature Review (SLR): Keberhasilan dan Kegagalan Kinerja Badan Usaha Milik Desa (BUMDES) - Ade Rani Aprillia; Dwi Cahyono; Ari Sita Nastiti (Politeknik Negeri Jember, 2021)
BUMDes has a role to realize the village economy. In improving the village economy, the government has the task of conducting socialization to the villagers through the provincial and district governments. The purpose of the systematic literature review is to determine the determinants of success and failure on the performance of BUMDes. Research data obtained from Google Scholar in 2016-2021 based on an initial search found as many as 484 articles and only 9 journals used as data sources and will be analyzed further. This study only uses research with a quantitative approach. The results of this study indicate that the failure factors that affect the performance of BUMDes are very diverse, namely motivation, education, age, and work experience. While the success factors that affect the performance of BUMDes are communication, AIS, HR, leadership style, motivation, work environment, salary, competence, organizational performance, commitment, organizational culture, training, the influence of job satisfaction, and GCG. Keywords: Systematic Literature Review; BUMDes; The Success Of BUMDes; BUMDes Failure